Population Pharmacokinetics and Dosing Regimen of Lithium in Chinese Patients With Bipolar Disorder - Jin, Zi-bin; Wu, Zhuo; Cui, Yi-fan; Liu, Xue-peng; Liang, Hong-bo; You, Jia-yong; Wang, Chen-yu (Frontiers in Pharmacology, 2022)
Background: Lithium is an effective medication approved for the treatment of bipolar disorder (BD). It has a narrow therapeutic index (TI) and requires therapeutic drug monitoring. This study aimed to conduct a population pharmacokinetics (PPK) analysis of lithium and investigate the appropriateness of the dosing regimen according to different patient characteristics.This study aimed to conduct a population pharmacokinetics analysis of lithium and investigate the appropriateness of the dosing regimen according to different patient characteristics. Methods: A total of 476 lithium concentrations from 268 patients with bipolar disorder were analyzed using nonlinear mixed-effects modeling. Monte Carlo simulations were employed to investigate the influence of covariates, such as weight, creatinine clearance, and daily doses of lithium concentrations and to determine the individualized dosing regimens for patients. Results: Lithium PK was described by a one-compartment model with first-order absorption and elimination processes. The typical estimated apparent clearance was 0.909 L/h-1 with 16.4% between-subject variability in the 62 kg patients with 116 mL/min creatinine clearance and 600 mg daily doses. To achieve target trough concentration (0.4-0.8mmol/L) in the maintenance phase, the regimen of 500 mg than 750 mg daily dose is recommended for patients with renal insufficiency and weighing 100 kg. Conclusion: A PPK model for lithium was developed to determine the influence of patient characteristics on lithium pharmacokinetics. Weight, creatinine clearance, and total daily dose of lithium can affect the drug’s clearance. These results demonstrate the nonlinear renal excretion of lithium; hence, dosage adjustments are recommended for patients with renal insufficiency.